Resolution of ethical conflicts between medical indications and patient preferences in case of unmarried woman with ovarian cancer: Penyelesaian Konflik Etika antara Indikasi Medik dan Preferensi Pasien pada Kasus Perempuan yang belum Menikah dengan Kanker Ovarium - Putri Irmayani; Kulsum Kulsum; Taufik S. Ismail (Indonesian Socety of Obstetrics and Gynecology, 2023)
Objectives: To resolve ethical conflicts in medical decision making in unmarried patients with a diagnosis of ovarian cancer. The ethical issue in this case is the main operative management in cases of ovarian cancer, namely removal of the uterus and both ovaries even though the patient is not married and has never been pregnant. The opportunity for patients to get pregnant no longer exists, so there is an ethical conflict between medical indications and patient preferences.Methods: This case report is about an unmarried woman 38- year with a diagnosis of ovarian cancer. This patient initially underwent right salfingooophorectomy surgery. Anatomical pathology results found adenocarcinoma serosum ovarii. The patient underwent chemotherapy for 3 cycles. Then the patient was re-operated with a planned debulking interval laparotomy.Discussion: From the aspect of patient indications, the results of combination treatment between surgery and chemotherapy have shown a marked increase in the survival rate of patients in five years. The choice of performing a debulking interval laparotomy is a difficult choice. The patient's preference to get pregnant will be difficult to accept, but it can be accommodated by improving the quality of life and paying attention to humanism, social and cultural aspects of its contextual features.Conclusion: Clinical ethical considerations related to uterine removal in unmarried patients is a matter of debate. Clinical ethical theory namely quality of life, patient preferences, medical indications, and contextual features are beneficial in medical decision making.Keywords: debulking intervals, ethical conflicts, medical indications, ovarian cancer, patient preferences.Tujuan: Untuk menyelesaikan konflik etik dalam pengambilan keputusan medik pada pasien yang belum menikah dengan diagnosis kanker ovarium. Isu etik pada kasus ini yaitu manajemen operatif utama pada kasuskanker ovarium yaitu pengangkatan uterus dan kedua ovarium padahal pasien belum menikah dan belum pernah hamil. Kesempatan untuk pasien untuk hamil tidak ada lagi sehingga terjadi pertentangan etik antara indikasi medik dengan preferensi pasien.Metode: Laporan kasus ini tentang seorang pasien perempuan yang belum menikah, berusia 38 tahun dengandiagnose kanker ovarium. Pasien ini awalnya dilakukan operasi salfingoooforektomi kanan. Hasil patologi anatomi ditemukan adenokarsinoma serosum ovari. Pasien menjalani kemoterapi sebanyak 3 siklus. Kemudian pasien dilakukan operasi kembali yang direncanakan tindakan laparotomi interval debulking.Diskusi: Dari aspek indikasi pasien, hasil pengobatan kombinasi antara pembedahan dan kemoterapi telahmenunjukkan peningkatan survival rate yang nyata pada pasien dalam lima tahun. Pilihan melakukan tindakanlaparotomi interval debulking merupakan pilihan sulit. Preferensi pasien untuk dapat hamil akan sulit dikabulkan, namun dapat diakomodir dengan peningkatan kualitas hidup dan memperhatikan aspek humanism, sosial dan kultural pada fitur kontekstualnya.Kesimpulan: Pertimbangan etik klinik yang berhubungan dengan pengangkatan rahim pada pasien yang belum menikah merupakan masalah yang diperdebatkan. Teori etika klinis yaitu indikasi medis, preferensi, kualitas hidup dan fitur kontektual sangat membantu dalam pengambilan keputusan medis yang etis.Kata kunci: indikasi medis, interval debulking, kanker ovarium, konflik etik, preferensi pasien